IDENTIFICATION OF FAULTS AND SLIP DIRECTIONS THROUGH A STUDY OF FOCAL MECHANISMS IN NORTH SUMATRA (2018-2024) - Ayu Lestari, Maysa Indah; Sirait, Ratni; Lubis, Lailatul Husna (Universitas Negeri Medan, 2026)
North Sumatra is located in the Ring of Fire zone, making it prone to earthquakes due to the convergence of the Indo-Australian and Eurasian plates, which form the 390 km long Sumatra Fault. This study aims to analyze the focal mechanism of earthquakes in North Sumatra during the period 2018-2024 using data from the Global Centroid Moment Tensor (GCMT). The analysis focuses on determining the type of earthquake mechanism, fault plane orientation, and slip direction and characteristics based on 21 earthquake events with magnitudes ranging from 4.8 to 5.4 Mw, analyzed using parameters such as location, time, depth, and nodal plane orientation. The results of the study indicate that earthquakes occurring in North Sumatra are dominated by strike-slip faults with horizontal movement. The orientation of the fault planes generally points northwest-southeast (NW-SE) and northeast-southwest (NE-SW), consistent with the characteristics of the Sumatra Fault and its segments, such as Renun, Toru, Barumun, and Angkola. Most of the earthquakes occurred at shallow to intermediate depths, posing a potential risk of damage in densely populated areas. These findings are expected to enhance regional geotectonic understanding and support earthquake disaster mitigation strategies in North Sumatra.